2022
DOI: 10.1002/ar.24946
|View full text |Cite
|
Sign up to set email alerts
|

Renal adaptation in relation to insectivorous feeding habit in the greater mouse‐eared bat, Myotis myotis (Chiroptera: Vespertilionidae)

Abstract: We examined the histological structure of the kidneys of Myotis myotis to better understand their structural adaptations to dietary habits. M. myotis is an insectivorous bat species that belongs to the family Vespertilionidae. The kidneys of M. myotis are unilobular, bean‐shaped, and surrounded by a renal capsule. The two parts are distinguished by a thin cortex and a thicker medulla. Renal corpuscles consist of the glomerulus and Bowman's capsule. The proximal tubule consists of cubic cells with a well‐develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…S3F). This is in line with previous reports that showed that fruit bats have a larger renal cortex and a smaller renal medulla compared to insectivorous bats ( 16, 17, 58 ). Additionally, we observed fruit bats to have significantly more type A intercalated cells, which are involved in acid secretion into the urine, and type B intercalated cells (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…S3F). This is in line with previous reports that showed that fruit bats have a larger renal cortex and a smaller renal medulla compared to insectivorous bats ( 16, 17, 58 ). Additionally, we observed fruit bats to have significantly more type A intercalated cells, which are involved in acid secretion into the urine, and type B intercalated cells (Fig.…”
Section: Resultssupporting
confidence: 93%
“…To our knowledge, our results provide for the first time an unbiased and comprehensive analysis of the cell-type compositions that distinguish insectivorous and frugivorous mammals. For the kidney, we find that the medullary and cortical differences observed between frugivorous and insectivorous kidneys (16,17,58) are due to specific nephron composition differences in DTL, TAL, connecting tubules, principal cells, type A intercalated cells, type B intercalated cells, and proximal tubules-like cells (Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
“…Bats are considered to fulfill a critical role as natural checks on insect populations (Ramírez‐Fráncel et al, 2022), and estimates of their monetary value (e.g., in lieu of pesticides) are immense (Riccucci & Lanza, 2014). As discussed in this issue by Paksuz (2023), a potential cost of insectivory is water loss, since insects have far lower water content than other food. In a histological study, Paksuz (2023) identifies microanatomical features of the kidneys in the insectivorous bat Myotis myotis that mitigate this potential water loss, such as a relatively large medullary region, where water is reclaimed and urine is concentrated.…”
Section: Dietmentioning
confidence: 99%
“…As discussed in this issue by Paksuz (2023), a potential cost of insectivory is water loss, since insects have far lower water content than other food. In a histological study, Paksuz (2023) identifies microanatomical features of the kidneys in the insectivorous bat Myotis myotis that mitigate this potential water loss, such as a relatively large medullary region, where water is reclaimed and urine is concentrated.…”
Section: Dietmentioning
confidence: 99%